Identification and Transcript Analysis of Differentially Expressed Genes from Floral Organs of Pigeon Orchid (Dendrobium Crumenatum) - Ng, Boon Zean (2007)
Dendrobium is a member of the Orchidaceae, which is one of the largest families of flowering plants. Over the centuries, orchid flowers have evolved with myriad forms and devices to attract particular pollinators. This led to the development of highly modified organs which not only contributed to the morphological diversity of orchid flowers, the success of pollination for some, but it also provided opportunities for accessing gene functions. Plant reproductive biology broadly comprises a network of biological events that represents a continuum of developmental processes beginning with the development and eventually culminating in the death of flowers. Due to the complex processes and biological mechanisms involved, analyses using molecular tools provided an opportunity to study the molecular elements that underlies the reproductive biology of orchids. This preliminary study was initiated to identify genes that are differentially expressed and putatively involved in the reproductive biology of the Pigeon orchid. Genes showing differential expression among the sepal, petal, lip and column of the Pigeon orchid were targeted using a derivative of the differential display technique known as GeneFishingTM technology. Ten differentially expressed transcripts were identified where sequence analyses revealed most of the transcripts include genes that were previously uncharacterized in the orchid system. Three partial cDNA clones which encode for small heat shock protein (A1C1-8), pectin methylesterase enzyme (A3C1-1) and 14-3-3 protein (A8C1-9) were selected for expression studies. Comparative expression profiling of these clones in other organs of the Pigeon orchid such as roots, stems and developing flower buds 3-4 days before anthesis via quantitative real-time RT-PCR revealed all three clones may putatively exhibit flower-specific expression. The results from realtime RT-PCR strongly suggest that these transcripts may possibly be involved in reproduction-related processes based on its localization in the column of the Pigeon orchid flowers.